PERLINDUNGAN HAK KONSUMEN DALAM PEMIKIRAN IBN TAYMIYYAH : ANALISIS ERA E- COMMERCE - Yulfira, Yumi; Nur Darwis, Fajar; Pradhana Sanjaya, Rezky (Universitas KH. A. Wahab Hasbullah, 2024)
This research examines consumer rights protection in Ibn Taymiyyah's view and its application in the e-commerce era. Consumer protection is an important aspect in maintaining fairness and honesty in business transactions. Ibn Taymiyyah, a great Islamic scholar, underscored the importance of justice ('adl), prohibition of fraud (gharar), and control of monopoly (ihtikar) to protect consumers. The aim of this research is to analyze the relevance and application of these principles in modern digital commerce. The research results show that Ibn Taymiyyah's principles can strengthen the consumer protection framework in the e-commerce era, increase trust and integrity of online markets, and support the development of policies that integrate Islamic business ethics with contemporary regulations.